Between two worlds : Jewish war brides after the Holocaust - Judd, Robin (The University of North Carolina Press, 2023)
"Facing the harrowing task of rebuilding a life in the wake of the Holocaust, many Jewish survivors, community and religious leaders, and Allied soldiers viewed marriage between Jewish women and military personnel as a way to move forward after unspeakable loss. Proponents believed that these unions were more than just a ticket out of war-torn Europe: they would help the Jewish people repopulate after the attempted annihilation of European Jewry. Historian Robin Judd, whose grandmother survived the Holocaust and married an American soldier after liberation, introduces us to the Jewish women who lived through genocide and went on to wed American, Canadian, and British military personnel after the war. She offers an intimate portrait of how these unions emerged and developed--from meeting and courtship to marriage and immigration to life in the United States, Canada, and the United Kingdom--and shows how they helped shape the postwar world by touching thousands of lives, including those of the chaplains who officiated their weddings, the Allied authorities whose policy decisions structured the couples' fates, and the bureaucrats involved in immigration and acculturation. The stories Judd tells are at once heartbreaking and restorative, and she vividly captures how the exhilaration of the brides' early romances coexisted with survivor's guilt, grief, and apprehension at the challenges of starting a new life in a new land." -- Provided by publisher.
Keywords: World War, 1939-1945 -- Women -- Europe.; Holocaust survivors -- Marriage.; Jewish women in the Holocaust.; War brides -- United States -- History -- 20th century.; War brides -- Canada -- History -- 20th century.; War brides -- Great Britain -- History -- 20th century.; Intercountry marriage -- History -- 20th century.; Jews -- Migrations.; Guerre mondiale, 1939-1945 -- Femmes -- Europe.; Juives pendant l'Holocauste.; Épouses de guerre -- États-Unis -- Histoire -- 20e siècle.; Épouses de guerre -- Canada -- Histoire -- 20e siècle.; Épouses de guerre -- Grande-Bretagne -- Histoire -- 20e siècle.; Mariage interethnique -- Histoire -- 20e siècle.; Juifs -- Migrations.; World War II.; Gender Studies.; SOCIAL SCIENCE.; Jewish Studies.; Military.; HISTORY.; Holocaust survivors -- Marriage; Intercountry marriage; Jewish women in the Holocaust; Jews -- Migrations; War brides; Women; Canada; Europe; Great Britain; United States; 1900-1999; Electronic books.; History